Amplifier design and analysis - Lim, Grace Si Qin (Nanyang Technological University, 2022)
Operational Amplifiers, known as op-amps, are voltage or current amplifying devices used with components like capacitors and resistors or inductors and many other electrical components. Operational amplifiers are multi-port network with different network parameters like scatter and hybrid of non-ideal cases of op amps. A two-port network is an electrical network to learn about the voltage and current characteristics of complex electrical networks. This project aims to calculate various parameters symbolically instead of numerically for two ports network and operation amplifiers for complex circuits. It also focuses on finding the voltage and current gain, as well as the input and output impedance of the 2 port networks. This can be done by applying basic op-amp two-port networks configurations for cascading connection using ABCD-parameters, parallel connection using Y-parameters and series connections using Z-parameter, combining all these operations to derive the final expression that has many elements.